Japan's new regional reality : geoeconomic strategy in the Asia-Pacific - Katada, Saori N. (Contemporary Asia in the world., 2020)
"Japan's New Regional Reality examines the transformation of Japan's regional economic strategy in the Asia Pacific in the last few decades, from the old mercantilist strategy to a new liberal one. It sheds light on the factors that define the active foreign policy of Prime Minister Shizo Abe in enabling this transformation. Saori N. Katada argues that this foreign policy evolution on the part of the Japanese government has emerged not only from geoeconomic challenges in the Asia Pacific with the rise of China, but also from the transformation of Japan's political economy as a "matured developmental state" where the state has lost direct control over the country's private sector activities. With globalization of Japanese businesses, the Japanese government is pushed to take a more liberal stance and be active in rule-making and regional institution-building in East Asia. In the context of leadership competition between the United States and China, Japan's strategic positioning will have a lasting impact on regional economic order and governance and positions Japan as an important regional player in the enduring competition between the United States and China for hegemony the Asia Pacific. This book is a comprehensive and groundbreaking analysis of the dynamics that have contributed to the economic and political outcomes in the region today"--